Combined Low-/High-Density Modern and Ancient Genome-Wide Data Document Genomic Admixture History of High-Altitude East Asians - Liu, Yan; Wang, Mengge; Chen, Pengyu; Wang, Zheng; Liu, Jing; Yao, Lilan; Wang, Fei; Tang, Renkuan; Zou, Xing; He, Guanglin (Frontiers in Genetics, 2021)
The Tibetan Plateau (TP) is considered to be one of the last terrestrial environments conquered by a modern human, understanding the genetic background of highland Tibetans plays a pivotal role in archeology, anthropology, genetics, and forensic investigations. Here, we genotyped twenty-two forensic genetic markers in 1,089 Tibetans residing in Nagqu prefecture and collected 1,233,013 Single Nucleotide Polymorphisms (SNPs) in highland East Asians (Sherpa and Tibetan) from the Simons Genome Diversity Project, ancient Tibetans from Nepal and Neolithic farmers from northeastern Qinghai-TP from public databases. We subsequently merged our two datasets with other worldwide reference populations or eastern ancient Eurasians to gain new insights into the genetic diversity, population movements and admixtures, as well as forensic characteristics of high-altitude East Asians and extend the Chinese National Database via comprehensive population genetic statistical tools (Principal Component Analysis (PCA), Multidimensional Scaling Plot (MDS), STRUCTURE/ADMIXTURE, f3, f4, qpWave/qpAdm and qpGraph). We identified 231 alleles with corresponding allele frequencies varying from 0.0005 to 0.5624 in the forensic low-density dataset, in which the combined powers of discrimination and the probability of exclusion were 1-1.22E-24 and 0.999999998, respectively. Additionally, comprehensive population comparisons in low-density data among 57 worldwide populations indicated that the highland Tibeto-Burman speakers kept the close genetic relationship with ethnically close populations. Findings from 1240K high-density dataset not only confirmed the close genetic connection between modern Highlanders, Nepal ancients (Samdzong, Mebrak and Chokhopani) and upper Yellow River Qijia people, suggesting the northeastern edge of TP served as a geographical corridor for ancient population migrations and interactions between highland and lowland regions, but also evidenced that late Neolithic millet farmers permanently colonized into the TP with adopting cold-tolerant barley agriculture was mediated via the acculturation of idea not the movement of people as no obvious western Eurasian admixture signals identified in our analyzed modern and ancient populations. Besides, results from qpAdm and qpGraph consistently demonstrated that all ancient and modern highland East Asians harbored shared deeply diverged Onge/Hoabinhian-related eastern Eurasian lineage, suggesting a common Paleolithic genetic legacy existed in high-altitude East Asians as the first layer of their gene pool.